Antinociceptive and Anti-Inflammatory Effects of Orally Administrated Denatured Naja Naja Atra Venom on Murine Rheumatoid Arthritis Models. (24th March 2013) - Zhu, Kou-Zhu; Liu, Yan-Li; Gu, Jin-Hua; Qin, Zheng-Hong
Abstract : To investigate the antinociceptive and anti-inflammatory activities of the denatured Naja Naja atra venom (NNAV) in rheumatoid arthritis-associated models, the denatured NNAV (heat treated; 30, 90, 270  μ g/kg), the native NNAV (untreated with heat; 90  μ g/kg), and Tripterygium wilfordii polyglycoside (TWP, 15 mg/kg) were administrated orally either prophylactically or therapeutically. We measured time of licking the affected paw in formaldehyde-induced inflammatory model, paw volume in egg-white-induced inflammation, and granuloma weight in formalin-soaked filter paper-induced granuloma. For adjuvant-induced arthritis (AIA) rats, paw edema, mechanical withdrawal threshold, serum levels of TNF- α and IL-10, and histopathological changes of the affected paw were assessed. We found that the denatured NNAV (90, 270  μ g/kg) significantly reduced time of licking paw, paw volume, and granuloma weight in above inflammatory models and also attenuated paw edema, mechanical hyperalgesia, and histopathology changes in AIA rats. Additionally, the increase in serum TNF- α and the decrease in serum IL-10 in AIA rats were reversed by the denatured NNAV. Although the native NNAV and TWP rendered the similar pharmacological actions on the above four models with less potency than that of the denatured NNAV, these findings demonstrate that oral administration of the denatured NNAV produces antinociceptive and anti-inflammatory activities on rheumatoid arthritis.